Inspiring best business practices / Dr. Basil Mustafa - Mustafa, Dr. Basil (Universiti Teknologi Mara Selangor, 2015)
The people of Turkey ought to be congratulated for their hard work in achieving a sustained record of economic stability with growth over the last decade or more. Unemployment rate, particularly given the continuous growth of workforce, and inflation, remain the significant challenges. Nevertheless, Turkey maintained its Gross Domestic Product (purchasing power parity) share of the world’s total and improved its GDP’s percentage on exports of goods and services. Turkey’s exports to the UK have been growing steadily from about $2billion in 2001 to about $8billion in 2010 with the exception of 2009. Turkish industries in various sectors have been producing quality goods. In view of the growing popularity of the oriental drink Turkish “coffee” and that of coffee houses in England, one of the most innovative products of Turkey is the coffeemaker. Ironically, a few centuries ago Turkish coffee was perceived as a challenge to the religious culture of England. Writers in Britain’s 17th century denounced coffee as conducive to sin, a drink that “could not have originated in paradise,…but in hell”.1 Now we all must wait with great expectation to see the British people discovering the influence of Turkish dessert kazandibi !